2004
DOI: 10.1002/cne.20015
|View full text |Cite
|
Sign up to set email alerts
|

PACAP mRNA is expressed in rat spinal cord neurons

Abstract: This study examines the expression of pituitary adenylate cyclase activating polypeptide (PACAP) mRNA in the rat spinal cord during normal conditions and in response to sciatic nerve transection. Previously, PACAP immunoreactivity has been found in fibers in the spinal cord dorsal horn and around the central canal and in neurons in the intermediolateral column (IML). Furthermore, in the dorsal root ganglia, PACAP immunoreactivity and PACAP mRNA expression have been observed preferentially in nerve cell bodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 86 publications
2
38
0
Order By: Relevance
“…PACAP peptides are potent trophic molecules and it is commonly proposed that an increased expression of PACAP peptides following injury may support neuronal survival and regeneration (Moller et al, 1997a,b;Zhou et al, 1999;Boeshore et al, 2004;Pettersson et al, 2004). PACAP can protect cardiomyocytes against oxidative stress-induced apoptosis (Gasz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PACAP peptides are potent trophic molecules and it is commonly proposed that an increased expression of PACAP peptides following injury may support neuronal survival and regeneration (Moller et al, 1997a,b;Zhou et al, 1999;Boeshore et al, 2004;Pettersson et al, 2004). PACAP can protect cardiomyocytes against oxidative stress-induced apoptosis (Gasz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In control peripheral nervous system structures, such as parasympathetic and sympathetic ganglia, dorsal root ganglia, vagal sensory ganglia and spinal and cranial motor nuclei, limited numbers of neurons exhibit PACAP immunoreactivity. However, PACAP expression increases markedly in these neurons following axotomy or explant culture (Zhang et al, 1995(Zhang et al, ,1996Moller et al, 1997a,b;Zhou et al, 1999;Pettersson et al, 2004). It is hypothesized that the increased expression of PACAP may be a response to injury that supports cell survival and regeneration (Moller et al, 1997a,b;Armstrong et al, 2003;Boeshore et al, 2004;Pettersson et al, 2004;Suarez et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PAC1 receptor is expressed mainly on neural and smooth muscle cells, while the VPAC1/VPAC2 are localized principally on the dorsal root ganglia (DRG), sensory nerve endings, and inflammatory cells [6,9,50,55,64]. The fact, that PACAP shows increased expression in the superficial layer of the spinal dorsal horn and in capsaicin-sensitive primary sensory neurons, suggested that it has a role in nociception [33,34,39,[61][62][63]. However, the results obtained from the early in vivo studies proved to be contradictory [41].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that systemic administration of PACAP can evoke sensitization and migraine-like attacks in migraineurs [27] is in line with the results of our animal experiments. Moreover, PACAP release in the dorsal horn has been reported in other experimental conditions of peripheral stimulation [126][127][128][129][130]. The potential relationship between PACAP and pain is enhanced by the co-localization and functional link of the NOS and PACAP systems, which has been described in a variety of studies [63,76,[131][132][133][134].…”
Section: Chemical Stimulation Of the Tsmentioning
confidence: 85%